Screening of alcohol-tolerant yeast of Saccharomyces cerevisiae - Wita Dewi Sondari; Achmad Ali Syamsuriputra; Tjandra Setiadi (Jurnal Teknik Kimia Indonesia, 2006)
In order to obtain culture of Saccharomyces cerevisiae which has the highest ethanol tolerance and can produce high yield of ethanol as well a study of mutation has been begun. Mutation experiment conducted by continuos adaptation on a chemostat was initiated with a preliminary study of screening of alcohol-tolerant yeast.  The procedures of screening of alcohol-tolerant yeast continued by optimation of substrate concentration and determination of its critical pH. Recently, the Laboratory of Microbiology and Bioprocess Technology Faculty of industrial Technology ITB has various kind of yeasts that have been obtained or isolated from various sources. The best culture for mutation has been chosen as the most ethanol tolerant one. By screening them on two types of experiment, has been obtained that culture Saccharomyces cerevisiae R-60 gave the highest external ethanol and internal ethanol   as well. External ethanol means the ethanol that was purposely added to the cultivation media, while the internal ethanol means the ethanol that was resulted from fermentation of the yeast.  As preparation for mutation experiment, the determination of optimum substrate concentration which can give the highest amount of Saccharomyces cerevisiae cells has been carried out. In order to set up the control point of culture viability on chemostat, the critical pH of choosed culture have also been obtained. The result of the experiment gave optimum glucose concentration of 18.6% and critical pH of 4.5 to 3.8, were to be applied in the mutation process.Keywords: Cultivation; Fermentation; Saccharomyces cerevisiae; Screening; YeastAbstrakPenelitian untuk mendapatkan kultur Saccharomyces cerevisiae yang mempunyai toleransi etanol yang tinggi dan dapat menghasilkan perolehan etanol yang juga tinggi telah dilangsungkan. Percobaan mutasi dilakukan dengan proses adaptasi secara kontinyu dalam chemostat yang diawali dengan suatu studi pendahuluan yang dinamakan skrining ragi tahan etanol. Prosedur skrining ragi tahan etanol ini dilanjutkan dengan optimasi kandungan substrat dan penentuan pH kritis-nya. Pada saat ini Laboratorium Mikrobiology dan Teknologi Bioproses Fakultas Teknologi Industri ITB telah memiliki berbagaijenis ragi yang berasal dari berbagai sumber. Kultur terbaik untuk mutasi dipilih sebagai kultur yang paling toleran terhadap etanol. Melalui percobaan screening ragi tahan etanol yang dilakukan dalam duajenis percobaan, diperoleh bahwa kultur Saccharomyces cerevisiae R-60 memiliki toleransi etanol eksternal dan internal paling tinggi. Etanol eksternal adalah etanol yang sengaja ditambahkan pada media kultivasi ragi, sementara etanol internal adalah etanol yang dihasilkan darijermentasi oleh ragi tersebut. Dalam mempersiapkan percobaan mutasi, penentuan konsentrasi substrat optimum yang dapat menghasilkan jumlah sel Saccharomyces cerevisiae terbesar telah dilakukan. Selain itu titik tetap via bilitas kultur da lam chemostatyang berupa pH kritis kultur pilihan juga telah ditentukan. Dari percobaan pendahuluan mutasi tersebut diperoleh konsentrasi glukosa optimum sebesar 18.6% dan pH ktitis kultur R-60 adalah 4.5 dan 3.8. Data tersebut akan diterapkan pada percobaan mutasi.Kata Kunci: Kultivasi; Fermentasi; Pre-mutasi; Ragi; Saccharomyces cerevisiae